Sex differences in the incidence of sudden cardiac arrest/death in competitive athletes: a systematic review and meta-analysis - Li, L.; Le Douairon Lahaye, S.; Ding, S.; Schnell, F. (Sports Medicine, 2025)
Background: Although many studies have demonstrated a lower incidence of sudden cardiac arrest or death (SCA/D) in female athletes than in male, there is limited understanding of the specific underlying causes. Objective: This systematic review aimed to assess the disparities in SCA/D incidence between male and female competitive athletes and explore the associated etiologies. Methods: A comprehensive search was conducted for retrospective and prospective studies examining SCA/D incidence in male and female athletes. Incidence and incidence rate ratios (IRRs) according to sex were evaluated. Results: Among the 16 studies analyzed, 1797 cases of SCA/D were observed; 1578 occurred in males (87.81%). Ages ranged from adolescent to adult. The incidence was 1.42/100,000 athlete-years (AY) in males (95% CI 0.97-2.09), and 0.32/100,000 AY in females (95% CI 0.17-0.59), resulting in an IRR of 5.55. When considering athletes aged = 35 years, the incidence was 1.46/100,000 AY in males (95% CI 0.91-2.34) and 0.30/100,000 AY in females (95% CI 0.14-0.66), with an IRR of 5.47. The IRR was 5.13 (95% CI 3.94-6.67) for the most recent studies with athletes enrolled only after the year 2000, versus 6.02 (95% CI 4.59-7.90) for the remaining studies covering all observed years. Hypertrophic cardiomyopathy (HCM) was the predominant cause among males (45.12%), while congenital coronary anomalies were more prevalent in females (33.04%). Conclusion: The incidence of SCA/D in females was approximately 6 times lower than in males, with sex differences also in the leading causes of SCA/D. Understanding these discrepancies could lead to targeted strategies for the prevention of SCD in athletes.